A New Ciboria sp. for Soil Mycoremediation and the Bacterial Contribution to the Depletion of Total Petroleum Hydrocarbons - Becarelli, Simone; Chicca, Ilaria; La China, Salvatore; Siracusa, Giovanna; Bardi, Alessandra; Gullo, Maria; Petroni, Giulio; Levin, David Bernard; Di Gregorio, Simona (Frontiers in Microbiology, 2021)
A Ciboria sp. strain (Phylum Ascomycota) was isolated from hydrocarbon polluted soil of an abandoned oil refinery in Italy. The strain was able to utilize diesel oil as a sole carbon source for growth. Laboratory-scale experiments were designed to evaluate the use of this fungal strain for treatment of the polluted soil. The concentration of Total Petroleum Hydrocarbons in the soil was 8538 mg/kg. Mesocosms containing the contaminated soil were inoculated with the fungal strain at 1% or 7%, on a fresh weight base ratio. After 90 days of incubation, the depletion of TPH contamination was of 78% with the 1% inoculant, and 99% with the 7% inoculant. 16S rDNA and ITS metabarcoding of the bacterial and fungal communities was performed in order to evaluate the potential synergism between fungi and bacteria in the bioremediation process. The functional metagenomic prediction indicated Arthrobacter, Dietzia, Brachybacerium, Brevibacterium, Gordonia, Leucobacter, Lysobacter and Agrobacterium sps. as generalist saprophytes, essential for the onset of hydrocarbonoclastic specialist bacterial species, identified as Streptomyces, Nocardoides, Pseudonocardia, Solirubrobacter, Parvibaculum, Rhodanobacter, Luteiomonas, Planomicrobium and Bacillus sps., involved in the Total Petroleum Hydrocarbons depletion. The fungal metabolism accelerated the onset of specialist over generalist bacteria. The capacity of the Ciboria sp. to deplete Total Petroleum Hydrocarbons in the soil in treatment was also ascertained.